Functional Analysis Diagrams with the representation of movement transitions - Lee,S; Jiang,P; Childs,P; Gilroy,K (2013)
A study on utilising a graphical interface to representmovement transmission within products has been conducted tosupport a creative conceptual design process that separates theconsideration of functional requirements and motionrequirements. In engineering design, many representations ofproduct structure have been proposed to assist in understandinghow a design is constituted. However, most of theserepresentations demonstrate only functions and are not able todemonstrate design structure. Functional Analysis Diagrams(FAD) provides a solution for this. An FAD shows not onlyfunctions but also physical elements by the network of blocksand arrows and thus it is capable of demonstrating varioustypes of information and the design scheme. This characteristicgives FADs an advantage for designers to combine differenttypes of information including useful and harmful interactionsto gain an overview of the design task. This study focuses onusing circles instead of arrows to represent movement attributesof mechanisms and machine elements in a KinematicFunctional Analysis Diagram (KFAD) and explores methods ofutilising it in mechanical design. A commercial case study ofmedical equipment design conducted with the assistance ofKFADs and a component database, mechanism and machineelements taxonomy (MMET), is described to illustrate theprocess. The design outcome shows that it is feasible to followthe proposed conceptual design process. With the help ofKFADs and the machine elements taxonomy to enableconsideration of movements, diverse considerations and designsolutions are possible.